Hubungan antara Profil Histomorfologik dengan Gambaran Endoskopi Esofagitis Refluks pada Dewasa - Intan Nevita Oktamia Bernanthos; Diah Rini Handjari (Majalah Patologi Indonesia, 2021)
BackgroundEarly diagnosis of GERD is very important because chronic reflux esophagitis is a major risk factor for Barrett esophagus, which is aprecursor lesion for esophageal adenocarcinoma. The aim of this study is to determine the frequency, demographic characteristics,histomorphological profile based on Esohisto criteria and endoscopic features of reflux esophagitis in FKUI/RSCM in 2016-2018.MethodsA cross-sectional study was conducted in Anatomical Pathology Department, Cipto Mangunkusumo General Hospital from January2016 to December 2018. Assessment criteria include demographic characteristics, histomorphological profiles, and endoscopicfeatures. Histomorphological assessment of reflux esophagitis in this study used the Esohisto criteria, by assessing basal cellhyperplasia, elevated papillae, dilated intercellular spaces and intraepithelial eosinophils. Assessment of the lesion severity isclassified as normal mucosa, mild lesion and severe lesion.ResultsThere were 65 cases of reflux esophagitis in adults over a period of 3 years in the Department of Anatomical PathologyFKUI/RSCM. Reviewing demographic data in January 2016-December 2018. The assessment criteria included demographiccharacteristics, histomorphological profiles, and endoscopic features. Histomorphological assessment of reflux esophagitis in thisstudy used the Esohisto criteria, by assessing basal cell hyperplasia, elevated papillae, dilated intercellular spaces in 65 casesfound 33 cases (50.8%) in men and 32 cases (49.2%) in women, with an average sample age of 56 years. The location of the mostlesions was distal esophagus in 30 cases (46.2%). Clinical manifestations in 13 cases (20%) were esophagitis. The most commonclinical symptoms were dysphagia in 21 cases (32.3%). Most endoscopic features were laryngopharyngeal reflux in 12 cases(18.5%), followed by grade C esophagitis in 9 cases (13.8%). The lesion severity of reflux esophagitis lesions based on Esohistocriteria found 37 cases (56.9%) mild lesion followed by severe lesion as many as 28 cases (43.1%)ConclusionThe Esohisto criteria can be used to help diagnose the lesion severity of reflux esophagitis with endoscopic pictures